The Merariq Tradition in Sasak Weddings in Kalijaga Village a Perspective Based on the Principle of Al-'Adah Muhakkamah - Wardah Wardah; Ahyat Habibi (Fakultas Agama Islam, 2026)
This study aims to analyze and classify the practice of the merariq tradition in Sasak marriages in Kalijaga Village, Aikmel District, East Lombok Regency, West Nusa Tenggara, from the perspective of the legal maxim al-‘ādah muḥakkamah. This research employed a qualitative approach using a field study design. Data were collected through online in-depth interviews, non-participant observation, and open-ended questionnaires administered to individuals who had participated in the merariq tradition as well as community members familiar with its implementation, selected through purposive sampling. The data were analyzed using the interactive model of Miles and Huberman, consisting of data reduction, data display, and conclusion drawing. The findings reveal that the merariq tradition in Kalijaga Village exhibits various forms of practice that continue to be recognized as part of the Sasak community’s cultural tradition. In general, the tradition fulfills the criteria of al-‘ādah muḥakkamah because it is practiced continuously and repeatedly, has been maintained across generations, and is carried out based on mutual community agreement. However, certain variations of the practice involve elements of khalwah, ikhtilāṭ, and excessive premarital interaction that are inconsistent with Islamic law. Consequently, the application of the maxim al-‘ādah muḥakkamah to the merariq tradition is partial and selective. This study contributes to the development of Islamic legal scholarship by proposing a classification of merariq practices based on the perspective of al-‘ādah muḥakkamah, thereby distinguishing between practices that should be preserved, those that require modification, and those that should be abandoned due to their inconsistency with Islamic legal principles.